APLIKASI MARKETPLACE BERBASIS SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMESANAN DAN PEMASANGAN IKLAN PADA BILLBOARD DI KOTA DENPASAR - I Made Dedi Pradnya Iswara; I Made Arsa Suyadnya; Putu Arya Mertasana (Program Studi Teknik Elektro UNUD, 2022)
Billboards are a great form of outdoor advertising. Billboards containing text or images ofinformation promoting a product are usually taken by the advertising agency. Advertisingcompanies promote curated billboards using individual websites, requiring clients to switchbetween sites to get billboards that meet the criteria. The purpose of marketplace creation is toavoid customers having to switch sites for billboards that meet the criteria. The marketplace isbuilt using Laravel 7 framework with additional features of a business intelligence system tohelp customers get billboards based on their criteria. The decision support system uses aweighted accumulation method that uses multiplication to relate the scoring criteria, where thescore of each criterion will be increased by the weight of the related criteria. The use of adecision support system with a weighted product approach as a support function on a marketsite is the use of a decision support system as a recommendation for the application market.The result of this research is that a web-based marketplace with a decision support system hasbeen successfully built using the Laravel 7 framework and MySQL DBMS. Based on the blackbox tests performed on the app, it performs according to its function and based on theoreticalcomparison testing related to the use of the weight product method, the results of therecommendations on the billboard application are in accordance with manual calculations.